Analisis Perundang-undangan: Kajian Kritis Undang-Undang Perbankan Syariah - Ichwan Ahnaz Alamudi Ichwan Ahnaz Alamudi (Yayasan Marwah Madani Riau, 2023)
Phenomenon in a relatively short period of time, Islamic banks stand hand in hand with the efforts of banking legislation, until finally Law No. 21 of 2008 on Sharia banking. The boom of sharia-based banking business in Indonesia, is also actually a form of Correction for conventional banks that operate with an interest system that is considered by some scholars as usury. Researchers provide a fundamental question that became the subject of the problem, namely how the form of legislation in Sharia banking legislation? This paper is a reflection on the problems that exist in the regulation of Islamic banking. This research is a type of literature study or in the world of law is called juridical-normative law Research. This study shows that the renewal aspect of Islamic banking regulation can be said to undergo periodic legal transformation, namely the period in 1992, the period in 1998 and the period in 2008. In 1992, banks introduced the concept of Islamic banking based on